2020
DOI: 10.3390/su12187437
|View full text |Cite
|
Sign up to set email alerts
|

Small & Medium-Sized Enterprises, Organizational Resilience Capacity and Flash Floods: Insights from a Literature Review

Abstract: From a managerial standpoint, sustainability poses numerous challenges for the business community. One of the prominent concerns in the context of organizational sustainability is the impact of climate change and extreme weather events (EWEs), which create discontinuity and damages to business operations. In this respect, small and medium-sized enterprises (SMEs) are particularly vulnerable to EWEs, such as flash floods, having disastrous consequences to SMEs that tend to be ill-prepared. Taking into considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 81 publications
(166 reference statements)
1
22
0
2
Order By: Relevance
“…Alam (2014) found that the vulnerability to, and risks of, drought were determined by farmers' economic conditions and the size of the farms owned by them [55]. Halkos (2019) demonstrated that small and medium sized entrepreneurs are disproportionately affected by EWEs [56], and Skouloudis et al (2020) found that small and medium-sized enterprises are particularly vulnerable to EWEs which is similar to the present study that the smallholder farmers face greater vulnerability to their farms, thus, greater risks [57]. Marginal farmers as well as smallholders typically have less options for managing the risks of hailstorms [19].…”
Section: Discussionsupporting
confidence: 82%
“…Alam (2014) found that the vulnerability to, and risks of, drought were determined by farmers' economic conditions and the size of the farms owned by them [55]. Halkos (2019) demonstrated that small and medium sized entrepreneurs are disproportionately affected by EWEs [56], and Skouloudis et al (2020) found that small and medium-sized enterprises are particularly vulnerable to EWEs which is similar to the present study that the smallholder farmers face greater vulnerability to their farms, thus, greater risks [57]. Marginal farmers as well as smallholders typically have less options for managing the risks of hailstorms [19].…”
Section: Discussionsupporting
confidence: 82%
“…It deals mainly with reactions to adversity and reflects the growing complexity and interdependence of socio-economic, financial and technological systems, the associated challenges for businesses and the need for solutions to deal with unexpected or unpredictable change [23]. According to [16,17,33,34], academic inquiry has been undertaken at organizational level as a response to external threats, employee-level resilience and strengths, but also at business models or supply chain levels in order to explore adaptability or design principles that reduce vulnerabilities and disruptions. Thus, setting the boundaries is a formidable challenge, because of the many forces and types of change, the interdependencies and the levels of systems that come into play when discussing resilience.…”
Section: Resiliencementioning
confidence: 99%
“…The institutional capacities are often shaped by political systems, especially in crisis and disasters [61]. It is a critical component for evaluating various factors that can encourage or discourage overall resilience against urban floods [62]. Public participation in awareness campaigns, presence of contingency, zoning and building regulations, emergency services, early warning, access to credit, etc., are the key determinants for institutional J o u r n a l P r e -p r o o f resilience to hazards [17,43].…”
Section: The Domains Of Resiliencementioning
confidence: 99%